2014
DOI: 10.1080/10503307.2014.896055
|View full text |Cite
|
Sign up to set email alerts
|

The role of therapists' treatment adherence, professional experience, therapeutic alliance, and clients' severity of psychological problems: Prediction of treatment outcome in eight different psychotherapy approaches. Preliminary results of a naturalistic study

Abstract: In this naturalistic study, 262 audiotaped psychotherapy sessions--randomly drawn from 81 individual therapies from eight different psychotherapy approaches--were rated completely on treatment adherence using a newly developed rating manual. In the therapy sessions, a relatively low percentage of treatment specific interventions (ranging from 4.2% to 27.8%) was found for all eight approaches, 50% to 73% of the interventions were nonspecific or common, and approximately 18% to 27% were intervention techniques f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
2
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 12 publications
1
49
2
7
Order By: Relevance
“…Building a good working relationship and setting common goals may facilitate adherence to the treatment protocol. These findings are similar to findings from previous studies on individual adult psychotherapy showing that alliance predicted adherence (Tschuschke et al., ; Weck et al., ). Moreover, the results are in accordance with the MST treatment manual, according to which an MST therapist should start by creating engagement and a positive working relationship, and formulating common treatment goals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Building a good working relationship and setting common goals may facilitate adherence to the treatment protocol. These findings are similar to findings from previous studies on individual adult psychotherapy showing that alliance predicted adherence (Tschuschke et al., ; Weck et al., ). Moreover, the results are in accordance with the MST treatment manual, according to which an MST therapist should start by creating engagement and a positive working relationship, and formulating common treatment goals.…”
Section: Discussionsupporting
confidence: 91%
“…Studies investigating the conjoint role of alliance and adherence have usually tested specific hypotheses regarding the mediating or moderating role of alliance on outcome, assessing alliance and adherence at a single point in time (e.g. Castonguay, Goldfried, Wiser, Raue, & Hayes, ; The Multisite Violence Prevention Project, ; Tschuschke et al., ; Webb et al., ). Yet, theoretical models argue that alliance and therapist adherence are essential in each phase of therapy and are interrelated all along (Goldfried & Davila, ; Hill, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on process variables in CBT for patients with binge-eating disorder (Brauhardt et al, 2014), patient and therapist characteristics did not predict therapist adherence to CBT. Other studies showed that a more positive working alliance as perceived by patients is associated with higher therapist adherence (Owen & Hilsenroth, 2011;Tschuschke et al, 2015;Weck, Grikscheit, Jakob, Höfling, & Stangier, 2015), whereas the direction of the interaction between adherence and the therapeutic alliance in predicting treatment outcomes seems to be inconsistent (Barber et al, 2006;Weck et al, 2015).…”
mentioning
confidence: 99%
“…The data were collected as part of a project promoted by the Swiss Charta for Psychotherapy, with the aim of investigating various process-outcome aspects of outpatient treatments (Tschuschke et al, 2015). In this non-randomized field study, therapies were carried out with different experiential and psychodynamic therapy methods.…”
Section: Methodsmentioning
confidence: 99%